Studi Komparasi Metode Talaqqi dan Metode Tilawati dalam Meningkatkan Kemampuan Membaca Al-qur’an - Salma Nadhifa Asy-Syahida; A. Mujahid Rasyid (Jurnal Pendidikan Islam Indonesia, 2020)
An educational institution has the responsibility for the process of educating children as students in reading and memorizing the Qur’an. Among the tasks that require extreme seriousness and extra care from every educator is the task of finding the best method to teach the student about Qur’an. This study aims to determine differences in the ability to read Qur’an between the students who use the Talaqqi method at Fitrah Insani SMPIT with students who use the Tilawati method at Salman Al-Farisi Middle School. The approach used in this research is a quantitative approach, which is by collecting data in the form of numbers. The sample used was 110 students. Data collection techniques such as interviews, observation, test and documentation studies. In analyzing the data using a sample independent t-test on the SPSS 15.0 application. Based on quantitative results, there are significant differences in the ability to read the Qur’an between students who use the Talaqqi method with students who use the Tilawati method. The mean value of students with the Talaqqi method was 87.6 while the average value of students who use the Tilawati method was 90.4, that students who use the Tilawati method get the higher scores than students who use the Talaqqi method. Students who use the Tilawati method are more fluent in reading the Qur’an with good and correct makharijul hurf and tajweed rules.